Effects of Collaboration Care Model on the Quality of Life in Patients after Coronary Angioplasty A Randomized Controlled Clinical Trial - Rezapoor, Parastoo Ms (International journal of community based nursing and midwifery, 2017)
BACKGROUND: Coronary artery diseases and therapies such as coronary angioplasty would lead to changes in the quality of life in patients. The aim of this study was to determine the effects of collaborative care model on the quality of life in patients after coronary angioplasty